The unfolding and refolding of human glutathione transferase A1-1. - Wallace, Louise Annette (My University, 1998)
The thermodynamic stability and the properties of the unfolding/refolding pathways of homodimeric human glutathione transferase A1-1 (hGST A1-1) were investigated. The conformational stability, assessed by urea- and temperature-induced denaturation studies, was consistent with a folded dimer/unfolded monomer transition with no stable intermediates. The high energy of stabilisation and the highly co-operative transition implies that the subunit-subunit interactions are necessary to maintain the three-dimensional state of the individual subunits. The stopped-flow-unfolding pathway, monitored using Trp fluorescence, was biphasic with a fast and slow unfolding event. Urea-dependence and thermodynamic activation parameters suggest that the transition state for each phase is well structured and is closely related to the native protein in term., of solvent exposure. The unfolding pathways monitored by energy transfer or direct excitation of AEDANS covalently linked to Cys111 in hGST A1-1 were monophasic with urea and temperature properties similar to those observed for the slow unfolding phase (described above). A two-step sequential unfolding mechanism involving the partial dissociation of the two structurally distinct domains per subunit followed by complete domain and subunit unfolding is proposed. The crystal structures of all cytosolic glutathione transferases show that the alpha helices 5, 6 and 7 pack tightly against each other to form the hydrophobic core of' domain II. Leu164 in class alpha glutathione transferase is a topologically conserved residue in the alpha helix 6. The replacement ofLeu164 with alanine did not impact on the functional or gross structural properties of hGST A1-1. The urea-induced equilibrium and kinetic unfolding pathways were similar to those observed for the wild-type protein. The free energy change of unfolding was equivalent to the energetic cost of deleting three methylene groups. Furthermore, the decreased co-operativity of the unfolding transition is consistent with a decrease in co-operativity of the forces that maintain the native state of hGST A1-1. The biphasic kinetic unfolding pathway indicated that the fast phase was destabilised to a greater extent than the slow unfolding phase. ( Abbreviations abstract)
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy.
Keywords: Glutathione transferase